Short Communication: Taxonomy and the first report for pollen and leaf surfaces anatomy of the genus Enkleia (Thymelaeaceae) in Thailand - Piyaporn Saensouik; Surapon Saensouk (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk P, Saensouk S. 2021. Short Communication: Taxonomy and the first report for pollen and leaf surfaces anatomy of the genus Enkleia (Thymelaeaceae) in Thailand. Biodiversitas 22: 1340-1344. Taxonomic of the genus Enkleia in Thailand are revised. Two species, Enkleia malaccensis Griff. and E. thorelii (Lecomte) Nevling, are reported. Enkleia siamensis (Kurz) Nevling and E. siamensis (Kurz) Nevling subsp. andamanica (Hutch. Ex C. E. Parkinson) Nevling are reduced to Enkleia malaccensis Griff.. Therefore, both species are recorded as synonym of E. malaccensis. E. thorelii is reported endemic to Thailand. Vernacular name, distribution data, ecological data, flowering period, fruiting period, conservation status, traditional use of this genus are provided. The pollen and leaf surfaces of the genus are examined and the first studied.